Agronomic character of several local genotypes of sorghum (Sorghum bicolor l.) at East Java. (May 2019) - Sulistyawati,; Roeswitawati, Dyah; Ibrahim, Jabal Tarik; Maftuchah,
Abstract: Sorghum classified as an annual crop that is very easy to be cultivated but its production until now classified as lagging compared to rice, corn and other cereals. In an effort to increase the fulfillment of food needs, sorghum plants can be developed in Indonesia as an alternative to local food other than rice. The development of sorghum plants is considered capable of supporting government programs to prevent the policy of importing rice and wheat. This study aims to determine the character of several genotypes of local sorghum East Java grown on paddy fields in Purutrejo Village, Purworejo Sub-District, Pasuruan City at an altitude of 5 m ASL with alluvial soil type. The average temperature is 29°C - 34°C with an average rainfall of 1430 mm / year. The study was conducted from June to August 2017. The experiments were arranged in a Randomized Block Design, using nine local sorghum genotypes replicated three times. Nine genotypes of local sorghum are Pasuruan, Lamongan 1, Lamongan 2, Tuban, Sampang 1, Sampang 2, Tulungagung 1, Tulungagung 2 and Jombang. The results showed that nine characterized genotypes had various agronomic characteristics on plant height, leaf number, stem diameter, panicle length, number of seeds per panicle, seed weight per panicle and 100 seed weight.